Hotels bars and lobbies - Berens, Carol (New York : McGraw-Hill, 1997)
This book is about: Lobbies, bars, and special rooms; Creating the fantasy; Making an entrance; ...
Keywords: Bars; Hotel lobbies; Drinking establishments; Hotel lobbies; Bars (Drinking establishments)